Influence of Dental Pulp Harvesting Method on the Viability and Differentiation Capacity of Adult Dental Pulp-Derived Mesenchymal Stem Cells - Victor Okada Vendramini; Sevda Pouraghaei; Rafael Maza Barbosa; Antônio Carlos Aloise; José Ricardo Ferreira Muniz; Marcelo Sperandio; Peter Karyen Moy; André Antonio Pelegrine; Alireza Moshaverinia (Hindawi Limited, 2021)
Objective. To compare two pulp harvesting methods for stem cell expansion, namely, conservative pulpotomy and pulpectomy from exodontia. Method. Ten freshly extracted sound third molars from five patients were selected. Five were used in the control group, where pulp harvesting was performed by exodontia and the remaining teeth were used in the test group, where the pulp was harvested by conservative pulpotomy (preserving the tooth). This was a split-mouth design study, where a third molar from one side was randomly allocated into the test group and the contralateral tooth in the control group. After pulp harvesting, the following evaluations were performed: cell morphology, sterility test, immunophenotyping, differentiation assays, first pass live cell counts, time to cryopreservation, and total number of expanded cells at the end of the fourth pass. Results. Regarding morphology, the cells from both groups presented a fibroblastic phenotype. All samples were sterile. Immunophenotyping demonstrated a positive expression for CD105, CD90, and CD73 and negative expression for CD45 in both groups. Differentiation assays were positive for osteogenic and chondrogenic differentiation in both groups. Regarding live cell counts in the first passage, the control group had 95.8% live cells in the total count and the test group 91.2% (p<0.05). The time required for cryopreservation was equivalent in both groups 51.6 days and 52.6 days, respectively (p>0.05). The total number of cells at the end of the fourth passage was 5,286,782 and 5,736,862, respectively (p>0.05). Conclusion. These results suggest that adult stem cell harvesting from conservative pulpotomy is as effective as the traditional exodontia-based method.